Restricting the Freedom of Enterprise – The Liability of Legal Entities and an Almost Irrational History in Germany - Beckemper, Katharina (2025)
Germany is one of the few countries that has not codified the penal liability of legal entities. This is mainly due to the fact that the dogmatic basis in Germany is different from that in many other countries. Nevertheless, the debate has been intense for many decades, with the main aim being to establish the dogmatic basis for the liability of legal entities. In recent years, however, the debate has taken a different direction. This is mainly due to international developments, but also to events in Germany itself. The Siemens case played a prominent role in this, raising the question, which has been the subject of intense debate in Germany, of whether the results of internal investigations may be seized by the public prosecutor’s office. The draft of the Penal Liability of Associations (Verbandssanktionengesetz) has devoted specific rules to this problem, which have no international precedent. This article traces the discussion in Germany and provides an insight into the failed project.